Head and Neck Surgery : Surgical Landmark and Dissection Guide - Mat Lazim, Norhafiza; Mohd Ismail, Zul Izhar; Abdullah, Baharudin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides concise critical points used during most types of head and neck surgeries combined with captivating figures and labeled photographs as well as live surgery photographs. Important head and neck surgery such as thyroid surgery, salivary glands surgery, sinonasal surgery, laryngeal surgery, and neck dissection are incorporated in this book. Each chapter starts with the anatomical description of the surgical structures with labelled photographs, in order to facilitate the reader's understanding the anatomic region of the surgical structures, the diseases related to the highlighted structures and its surgery. The specific type of surgeries indicated for specific diseases are provided and discussed in a concise manner. Surgical procedures have also been presented in a clear and easily comprehensible manner using both important anatomical and surgical landmarks. Attractive labels and arrows are inserted alongside the figures. This book will be an excellent guide book especially for both undergraduate and postgraduate students, junior surgeons, clinicians, anatomy dissectors, scientists, as well as general academia. It will also be a valuable reference source for the junior head and neck surgeons and trainees in the head and neck surgical oncology specialty. .
Introduction -- Principle of head and neck surgery and the importance of anatomical characteristics -- Significance of anatomical versus surgical landmarks in head and neck surgery -- Radiological Assessment and Its Roles in Head and Neck Surgical Oncology -- Approach Towards Oral Cavity Cancers -- Oropharyngeal and Hypopharyngeal Tumours and Its related surgery -- Surgical Management of Nasopharyngeal Carcinoma -- Salivary glands Disease and Tumours and Its Surgery -- Thyroid glands Tumour and the Surgery -- Endoscopic Nasal, Paranasal sinuses and Skull Base surgery -- Surgical Approaches to the Maxilla, Maxillary Sinus, Pterygopalatine Fossa, and Infratemporal Fossa for Malignant Tumors -- Laryngeal Disease and Tumours and Its Related Surgery -- Neck Dissections in head and neck surgery -- Head and Neck Surgical Access, mandibulotomy and mandibulectomyin head and neck surgical oncology -- Orbital Exenterationin Head and Neck surgery -- Temporal Bone Diseases and Tumours and Its Related Surgery -- Pediatric Head and Neck Tumours and its Surgery -- Miscellaneous Head and Neck Surgery -- Controversies and Updates in the management of head and neck malignancy.
Keywords: Surgery; Medicine; Surgery; Clinical Medicine; Head -- surgery; Neck -- surgery